2021
DOI: 10.1186/s12967-021-02973-5
|View full text |Cite
|
Sign up to set email alerts
|

Using genetic variants to evaluate the causal effect of serum vitamin D concentration on COVID-19 susceptibility, severity and hospitalization traits: a Mendelian randomization study

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has struck globally and is exerting a devastating toll on humans. The pandemic has led to calls for widespread vitamin D supplementation in public. However, evidence supporting the role of vitamin D in the COVID-19 pandemic remains controversial. Methods We performed a two-sample Mendelian randomization (MR) analysis to analyze the causal effect of the 25-hydroxyvitamin D [25(OH)D] concent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 52 publications
2
31
0
Order By: Relevance
“…Mendelian randomization studies have explored the role of a wide range of anthropometrics and biomarkers in COVID-19 risk, including anthropometrics, blood pressure, coagulation factors, cytokines, inflammatory markers, glycaemic traits, haematological traits, lipids, liver functions, renal functions and vitamins. 27 , 31–33 , 35 , 38–40 , 42 , 44–47 , 49 , 52 , 53 , 55 , 58–60 , 62 , 64 , 65 Consistent evidence suggested that obesity [higher body mass index (BMI) and trunk fat ratio] was associated with higher COVID-19 risk 27 , 32 , 38 , 42 , 45 , 53 and one study also showed that increase in height was associated with higher risk of COVID-19 susceptibility. 27 Consistent evidence showed systolic and diastolic blood pressure to have no role in COVID-19 risk, 27 , 32 , 42 , 49 , 53 although one study found that higher pulse pressure was associated with higher risk of COVID-19 hospitalization in people of mixed ancestry but not of European ancestry.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Mendelian randomization studies have explored the role of a wide range of anthropometrics and biomarkers in COVID-19 risk, including anthropometrics, blood pressure, coagulation factors, cytokines, inflammatory markers, glycaemic traits, haematological traits, lipids, liver functions, renal functions and vitamins. 27 , 31–33 , 35 , 38–40 , 42 , 44–47 , 49 , 52 , 53 , 55 , 58–60 , 62 , 64 , 65 Consistent evidence suggested that obesity [higher body mass index (BMI) and trunk fat ratio] was associated with higher COVID-19 risk 27 , 32 , 38 , 42 , 45 , 53 and one study also showed that increase in height was associated with higher risk of COVID-19 susceptibility. 27 Consistent evidence showed systolic and diastolic blood pressure to have no role in COVID-19 risk, 27 , 32 , 42 , 49 , 53 although one study found that higher pulse pressure was associated with higher risk of COVID-19 hospitalization in people of mixed ancestry but not of European ancestry.…”
Section: Resultsmentioning
confidence: 96%
“… 59 , 65 No evidence was found for the role of leukocyte telomere length (a determinant of longevity) in COVID-19. 60 Consistent evidence showed that glycaemic traits (HbA 1c , fasting insulin, fasting glucose and 2-h glucose), 31 , 32 , 42 high density lipoprotein (HDL) cholesterol and apolipoprotein A, 27 , 32 , 39 , 42 , 62 , 65 renal traits [creatinine-based estimated glomerular filtration rate (eGFR) and serum creatinine] 27 , 42 , 59 and vitamins C and D 27 , 33 , 35 , 40 , 46 , 47 , 52 were not associated with risk of COVID-19 ( Supplementary Table S1 , available as Supplementary data at IJE online).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a Mendelian randomization study [ 102 ] found that low VD levels are not casually associated with Covid-19 susceptibility and severity.…”
Section: Limitationsmentioning
confidence: 99%
“…There may be several explanations for the discrepancy between epidemiological observations and the non-significant causal relationship between genetically predicted LTL and COVID-19 severity in our study. On one hand, it is important to note that such observational studies, despite attempts to adjust for potential confounding factors, have the possibility of significant residual confounding factors due to uncontrolled or imperfectly measured covariates ( Cui and Tian, 2021 ). In particular, care must be taken to control for potential factors that might influence TL, such as technical variations in TL measurement, psychological stress, income, marital status, lifestyle, and cell-type composition ( Demanelis et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%